323 The Role of the Temporal Pole in Temporal Lobe Seizure Networks: An Intracranial Electrode Investigation. (August 2016) - Abel, Taylor J.; Woodroffe, Royce; Moritani, Toshio; Kirby, Patricia; Howard, Matthew A.; Kawasaki, Hiroto; Werz, Mary Ann
Abstract : INTRODUCTION: A convergence of clinical research suggests that the temporal pole (TP) plays an important, and potentially underappreciated, role in the genesis and propagation of seizures in temporal lobe epilepsy (TLE). Understanding the role of the TP in TLE is becoming increasingly important because selective surgical resections for medically intractable TLE spare TP cortex. The purpose of this study is to characterize the role of temporopolar cortex in TLE using dense electrocorticographic (ECoG) recordings of the TP in patients undergoing invasive monitoring for medically intractable TLE. METHODS: In 10 consecutive patients with medically intractable epilepsy who would eventually undergo corticoamygdalohippocampectomy (CAH), chronic ECoG recordings of the TP were obtained using an array customized to provide dense coverage of the TP as part of invasive monitoring. A retrospective review of clinical records including ECoG, neuroimaging, neuropathology, and clinical outcomes was performed. RESULTS: In 5 patients (50%) the TP was involved at seizure onset, and, in 2 patients (20%), seizures spread to the TP within 2 seconds. One additional patient had subclinical seizures arising from the TP. In the 2 remaining patients, seizures began in the mesial temporal lobe with late spread to the TP. Seizure onset in the TP did not correlate with preoperative neuroimaging abnormalities of the TP. CONCLUSION: These data demonstrate that TP cortex plays a crucial role in temporal lobe seizure networks. Our results, in conjunction with other clinical studies, suggest that seizures originating from the TP are a possible reason for poor seizure control after selective amygdalohippocampectomy.